URGENSI PERAN SERTA MASYARAKAT DALAM MENDUKUNG IMPLEMENTASI KONSEP SAPTA PESONA DESA WONOSOCO UNDAAN KUDUS - Rochanah, Rochanah; Hikmah, Nuzilatul (Institut Agama Islam Negeri (IAIN) Kudus, 2021)
Wonosoco Village is one of several tourist areas being developed in Kudus City. Wonosoco Village is located in Undaan District, Kudus Regency, Central Java Province. In an effort to support the realization of the vision of the Wonosoco village government as an agricultural village and tourist destination, the participation of the community is urgent in supporting the implementation of Sapta Pesona. This research is a field research with a descriptive analytical qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The problems raised in this research are; How is the participation of the community in supporting the implementation of Sapta Pesona. The results of the study indicate that the participation of the Wonosoco village community in supporting the implementation of Sapta Pesona Aman is; not behaving in a manner that creates fear in visitors, being alert in taking care of visitors, sharing comprehensive information regarding tourist attractions, and minimizing accidents. 2) Orderly; Get used to the queuing culture, comply with applicable regulations and appeals. Applying time discipline. 3) Clean; maintain environmental cleanliness by providing trash cans, maintaining cleanliness of public facilities, maintaining air cleanliness, providing clean and hygienic culinary. 4) Cool; Carry out reforestation, maintain properly the reforestation program. 5) Beautiful; Maintaining environmental sustainability, attractive environmental management. 6) Friendly; Showing a humble attitude, Standby in providing help, Sharing information about customs that are still being preserved, being respectful and tolerant. 7) Memories; Presents a slick and interesting panorama. Souvenirs.